Implementasi Pengabdian Masyarakat melalui Pemberian Waktu Belajar Tambahan (LES) di SMP Negeri 2 Kartasura - Andrian Iswanto (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Since the spread of Covid-19 in Indonesia decreased in early 2022, the transition from online learning and limited face-to-face in schools began to gradually return to full face-to-face. SMP Negeri 2 Kartasura is one of the schools that implemented the policy. However, the problem is the decline in student enthusiasm and motivation in participating in learning and the material that has been taught during online learning has not been understood by students. Through the "Komadiksi Mengajar" activity organized by the KOMADIKSI SMART UNS Student Activity Unit, the author conducted community service through learning assistance by providing study time at SMP Negeri 2 Kartasura. The provision of study time (LES) is one of the efforts to implement the tri dharma of higher education in community service. This is done to increase student motivation and interest in learning activities. The method of providing study time used is by providing learning assistance directly after school. After discussing with the principal, the author and the team were directed to assist students who would be entered in the water rocket competition. The target to be achieved in this community service is to increase the interest and motivation of SMP Negeri 2 Kartasura students in learning and increase academic and non-academic achievements. As a result, students become enthusiastic and motivated to continue learning and achieving both academic and non-academic according to their interests and talents.